Upaya Pembelajaran Bahasa Asing (Arab & Inggris) terhadap Skill Komunikasi Santri di Pondok Pesantren Modern An-Nursali Binjai - Devy Anggreny; Syahrul Holid (Departement of Mathematics Education, 2024)
In the current era of globalization, learning foreign languages ​​(Arabic & English) has become a necessity for every student in Islamic boarding schools. Not only adults, but foreign languages ​​have been taught from children to foreign language skills in Islamic boarding schools, which really supports them in other knowledge, especially books in Arabic and English. Santri in the current millennial era must be able to do everything, in the field of da'wah in the general public and in their own families. Therefore, students must be skilled in communicating well and using two languages, namely Arabic and English at the An Nursali Modern Islamic Boarding School. This journal discusses the foreign language communication skill methods applied at the An Nursali Islamic Boarding School. This method involves collecting data by observing their learning and daily activities. Based on the results of research conducted, it was concluded that foreign language learning at the An Nursali Modern Islamic Boarding School uses a curriculum prepared independently by the teachers because it is still local content, not national content.